Leveraging New Business Models to Enhance Profitability in Cohort-Based Courses Edtech Businesses Study Case: PT Dibimbing Digital Indonesia - Syah, Zaky Muhammad; Prasetio, Eko Agus; Hutajulu, Sahat (Syntax Literate, 2024)
Over the past five years, the education technology (EdTech) sector has gained increasing prominence, characterized by significant growth in investments, transactions, and overall revenues. PT Dibimbing (Dibimbing.id), an EdTech company, experienced a decline in revenue largely attributed to elevated customer acquisition costs (CAC). This research aims to analyze the challenges faced by Dibimbing.id and form an innovative and profitable business model for Dibimbing.id. This study uses qualitative research by applying Richardson's framework theory (Value Oriented Framework). This research was obtained through in-depth interviews and Forum Group Discussions (FGDs). The FGD involved teams in Dibimbing.id, including marketing and sales, development, operations, human resources, finance, and technology teams. The results showed that the existing business model faces problems such as variable learning speed, highly complex learning syllabus, hiring difficulties to find advanced talents, bootcamp business model that does not contribute to profit growth, students' concerns with limited job prospects, and financial constraints. Therefore, four solutions were revealed in this research for a new business model, namely self-paced learning, leveling course, job guarantee program, and Study Now Pay Later (SNPL).